FAKTOR YANG MEMENGARUHI LEVERAGE SEKTOR TEKNOLOGI DI BEI PERIODE 2019 – 2023 - AMELITA AGUSTINA; BENY (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study aims to analyze the factors that influence the level of leverage of technology sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. The independent variables in this study include profitability, tangible assets, company size, non-debt tax shield, and liquidity, while the dependent variable analyzed is leverage. This research was conducted to find out how these factors affect the leverage level of technology companies. The object of this research is companies in the technology sector and listed on the IDX. The sample used in this study amounted to 70 data obtained from the company's annual financial statements selected using a purposive sampling method. The collected data were analyzed using the regression analysis method to identify the effect of the independent variable on the dependent variable. The results of data analysis show that profitability, tangible assets, non-debt tax shield, and liquidity have an impact on leverage. While company size has no impact on leverage. The results of this study can be taken into consideration for companies in managing leverage to optimize finance, minimize risk and increase firm value by taking into company characteristics.